Mechanical response of slender ultra-high-strength concrete filled high-strength steel tube columns under eccentric compression - Xia Luo; Xinye Yu; Jiangang Wei; Chenchen Jiang; Yan Yang (Case Studies in Construction Materials)
This study bridges the knowledge gap regarding the eccentric compression behavior of circular ultra-high-strength concrete filled high-strength steel tube (CuFShT) columns. Tests on 12 medium-length CuFShT specimens with varying steel contents and load eccentricities revealed their failure modes, load-deflection responses, and steel strains. Finite element models were developed to analyze the effects of load eccentricity, slenderness ratio, and cross-sectional parameters on the ultimate load-bearing capacity. Calculation methods for the ultimate capacity, including an evaluation of existing design codes, are discussed, and an explicit method for engineering applications is proposed. The results show that an increased steel content enhances the flexural stiffness and load-bearing capacity, whereas a higher eccentricity significantly reduces the load-bearing capacity. The combined influence of the eccentricity and slenderness ratio suggests the need for an overall reduction factor in the design calculations. After normalizing the slenderness, the cross-sectional parameters showed a minimal impact. Among the existing design codes, including AISC 360–16, AIJ-2008, and T/CECS 987–2021, the European standard EN 1994–1–1 provides the most accurate predictions for CuFShT columns. By incorporating the Perry-Robertson formula, the coupled effects of the eccentricity and slenderness ratio were effectively captured, enabling a precise estimation of the ultimate load-bearing capacity for eccentrically-compressed CuFShT columns using the explicit calculation formula.